Algeria : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
Algeria's 2004 Article IV Consultation reports that the fiscal expansion has contributed to job creation, but unemployment remains high. The vulnerability of public finances to oil price fluctuations has increased and monetary policy has helped to keep inflation under control. Sound management of high external inflows from hydrocarbon exports is the key to improve the outlook for private sector-driven economic growth and employment. The fiscal adjustment planned by the government will gradually bring the nonhydrocarbon primary deficit to a sustainable level.